1996
DOI: 10.1002/j.1460-2075.1996.tb00872.x
|View full text |Cite
|
Sign up to set email alerts
|

The second immunoglobulin-like domain of the VEGF tyrosine kinase receptor Flt-1 determines ligand binding and may initiate a signal transduction cascade.

Abstract: Vascular endothelial growth factor (VEGF) is an angiogenic inducer that mediates its effects through two high affinity receptor tyrosine kinases, Flt‐1 and KDR. Flt‐1 is required for endothelial cell morphogenesis whereas KDR is involved primarily in mitogenesis. Flt‐1 has an alternative ligand, placenta growth factor (PlGF). Both Flt‐1 and KDR have seven immunoglobulin (Ig)‐like domains in the extracellular domain. The significance and function of these domains for ligand binding and receptor activation are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
98
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(106 citation statements)
references
References 44 publications
6
98
0
2
Order By: Relevance
“…In this study, we have developed several novel hybrid molecules that inhibit VEGF in vitro and are capable of inhibiting ocular neovascularization in vivo. It has been reported that domain 2 of VEGFR Flt-1 requires the presence of flanking sequences from Novel anti-VEGF chimeric molecules P Pechan et al dimerization of the soluble receptor, we constructed Flt-1 domain 2 linked directly to IgG1-Fc fragment (molecule D2-Fc), but such a strategy did not enhance its binding to VEGF, in agreement with Davis-Smyth et al 13 We then have linked the second domain of Flt-1 to Fc through a 9Gly linker, and thus generated a novel molecule, sFLT01, with potent VEGF binding. Our results show, for the first time, that Flt-1 domain 2 does not require presence of other VEGFR domains for high-affinity VEGF binding.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In this study, we have developed several novel hybrid molecules that inhibit VEGF in vitro and are capable of inhibiting ocular neovascularization in vivo. It has been reported that domain 2 of VEGFR Flt-1 requires the presence of flanking sequences from Novel anti-VEGF chimeric molecules P Pechan et al dimerization of the soluble receptor, we constructed Flt-1 domain 2 linked directly to IgG1-Fc fragment (molecule D2-Fc), but such a strategy did not enhance its binding to VEGF, in agreement with Davis-Smyth et al 13 We then have linked the second domain of Flt-1 to Fc through a 9Gly linker, and thus generated a novel molecule, sFLT01, with potent VEGF binding. Our results show, for the first time, that Flt-1 domain 2 does not require presence of other VEGFR domains for high-affinity VEGF binding.…”
Section: Discussionsupporting
confidence: 82%
“…13 The molecule Flt(1-3)-IgG was reported to have the same VEGF-binding affinity as Flt(1-7)-IgG, however Flt(2)-IgG that contains only second domain was not capable of inhibiting VEGF. 13,17 Another molecule called VEGF-Trap, generated by the second domain of Flt-1 fused to the third domain of KDR and human IgG1-Fc region, has been shown to be a very potent VEGF binder. 18 Adeno-associated virus (AAV) vectors offer an attractive tool for intraocular gene delivery because of their nonpathogenic nature, low toxicity, minimal immunogenicity and long-term persistence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…KDR/Flk-1 is required mainly for mitogenic and chemotactic responses, whereas Flt-1 contributes to endothelial cell morphogenesis. 12,13 Recently, the intracellular signaling pathways mediating these effects downstream of KDR/Flk-1 activation have been identified. KDR/Flk-1 induces proliferation through activation of the extracellular signalregulated kinase (ERK) 1/2 pathway leading to gene transcription 14 and endothelial cell survival through phosphatidylinositol 3-kinase activation, resulting in increased lipid phosphatidylinositol (3,4,5)P 3 and activation of several important intracellular molecules, such as Akt and the small GTP-binding protein, Rac.…”
mentioning
confidence: 99%